Environmental ethics - Boylan, Michael 1952- (Wiley Blackwell, 2022)
"In 2007 when I was a senior research fellow at The Center for American Progress, a progressive policy think tank in Washington, D.C., I spent some time on the Environmental Policy Team. This team had as it's goal the creation of various papers that would be listed on the Center's website and distributed to appropriate committees in Congress to influence public policy. At the time it did seem like the country and the world was on the way to combatting the causes of global warming: CO2 and other chemical emissions that were creating a "greenhouse" effect that was moving us to climate disaster. In 2009 there was the Copenhagen Climate Change Conference in which plans were laid for creating a cooperative international structure for implementing some of the policy recommendations of the Kyoto Protocol (1997). Progress was made to identify options for various countries to play their part in this project (the details to be negotiated later) and a goal was set to respond to climate change in the short and long term. To this end, a "red line" was established to avoid allowing the average global temperature to rise 2 degrees Celsius above pre-industrial levels. Procedurally, developed countries like the United States promised certain levels of funding so that the goals might be achievable for poorer countries. Methods of measurement were agreed upon and finally there were new agencies created under the auspices of the United Nations to help administer and monitor these goals"--Provided by publisher.